Goat Science 2018
DOI: 10.5772/intechopen.74203
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism in Goats: Husbandry Management, Range Management, Gut Immunity and Therapeutics

Abstract: Goats play a vital role in the economy of common man. It acts as pivotal point in the uplift of socio-economic status of females. The goats are such delicate and fragile animals that encounter a lot of infectious and non-infectious diseases including viruses, bacteria and gastrointestinal parasites (GIP). The goat being a range animal is selective feeder. It needs a lot of managemental practices which safeguards its health. This chapter focuses on management, impact of gastrointestinal parasites, role of intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…One of the directions of combating nematodoses is the use of medicinal plants (Ayaz et al, 2018;Oliveira Santos et al, 2019;Swargiary et al, 2020). They are used in both in vitro (De Paula Carlis et al, 2019;Esteban-Ballesteros et al, 2019;Maestrini et al, 2019;Piza et al, 2019;, and in vivo experiments (Sastya et al, 2018;Alowanou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…One of the directions of combating nematodoses is the use of medicinal plants (Ayaz et al, 2018;Oliveira Santos et al, 2019;Swargiary et al, 2020). They are used in both in vitro (De Paula Carlis et al, 2019;Esteban-Ballesteros et al, 2019;Maestrini et al, 2019;Piza et al, 2019;, and in vivo experiments (Sastya et al, 2018;Alowanou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Helminthiasis and protozoasis of ruminants can have a fairly significant effect on the violation of the physiological state of animals [6][7][8]15], subsequently this is reflected in a decrease in the level of dairy and meat productivity, the growth rate of young animals and other indicators [6][7][8]. Unfortunately, the prevention of invasive diseases does not receive due attention from managers and veterinarians of farms, despite the wide variety of anthelmintic 7preparations [9-10, 12, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Goat farming is gaining traction in the commercial and domestic sectors over the last few years due to its popularity. However, as goat meat and milk are generally recognised worldwide, constraints on the growth of goat enterprises have also been observed due to its association with bacterial (Miller and Lu 2019) and parasitic infections (Ayaz et al 2018) that are critical for causing human infections (Monteiro et al 2018) and may pose a threat to public health by spreading zoonotic diseases. A retrospective study on goat from 1988 to 2012 showed that 43.67% of deaths were due to enteritis, followed by gastrointestinal parasitism and gastric diseases (Pawaiya et al 2017).…”
Section: Introductionmentioning
confidence: 99%